Moral judgment in Religious Character Education: Applying Rest’s Four-Component Model in MTsN 2 Bandar Lampung, Indonesia - Muarafa Nur Afif; Novri Rahman; Chairul Anwar (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
This study aims to explore the processes of moral reasoning (moral judgment) among students in the context of religious character education at MTsN 2 Bandar Lampung and to identify the factors that influence it. Using a qualitative case study design, the research involved 28 eighth-grade students, teachers, and the school principal, selected purposively. Data were collected through participatory observation of religious activities, semi-structured interviews, moral vignettes, and document analysis. Data analysis employed the interactive model of Miles and Huberman. In contrast, data validity was ensured through source triangulation and member checking. The findings show that students’ moral judgment develops through the integration of religious experiences, spiritual habituation, and teacher role modelling. In social studies learning, activities such as socio-religious discussions, reflections on justice, and linking social phenomena to Islamic moral principles are essential for fostering students’ ethical decision-making abilities. Religious practices serve as reflective spaces for students to evaluate their actions in light of ethical and religious considerations. Honesty and justice emerge as the primary foundations of their moral reasoning, indicating a shift from the conventional to the post-conventional stage. Thus, students’ moral judgment is shaped not only by religious rituals but also by contextual and reflective social studies instruction. The integration of religious and social values strengthens the role of the madrasah as a space for cultivating transcendental morality and social awareness, demonstrating the relevance of Rest’s Four Component Model. Keywords: Moral Judgment, Religious Character Education, Social Studies